2005
DOI: 10.1161/01.hyp.0000161875.32767.ac
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Peripheral Chemoreceptors Deactivation on Sympathetic Activity in Heart Transplant Recipients

Abstract: Abstract-Heart transplantation initially normalizes sympathetic hyperactivity directed at the muscle circulation. However, sympathetic activity increases with time after transplantation and the exact mechanisms responsible for sympathetic control in heart transplant recipients remain unclear. We examined the effects of peripheral chemoreflex deactivation caused by breathing 100% oxygen on muscle sympathetic nerve activity (expressed as number of burst per minute and mean burst amplitude), heart rate, and mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 52 publications
2
30
0
1
Order By: Relevance
“…Only one study till now has reported that the deactivation of carotid body chemoreceptors may decrease sympathetic activation in systemic hypertension. 18 Hypertensive patient 100 % Oxygen 21 % Oxygen Tonic chemoreflex activation in hypertension M Siński et al However, in this study patients were of an advanced age and on antihypertensive medication, which may influence sympathetic activity. In the recent study by Binggeli et al, 19 the authors used hyperoxic stimuli in hypertensive subjects with and without periodic breathing, and did not find a significant reduction of MSNA in the group without periodic breathing.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…Only one study till now has reported that the deactivation of carotid body chemoreceptors may decrease sympathetic activation in systemic hypertension. 18 Hypertensive patient 100 % Oxygen 21 % Oxygen Tonic chemoreflex activation in hypertension M Siński et al However, in this study patients were of an advanced age and on antihypertensive medication, which may influence sympathetic activity. In the recent study by Binggeli et al, 19 the authors used hyperoxic stimuli in hypertensive subjects with and without periodic breathing, and did not find a significant reduction of MSNA in the group without periodic breathing.…”
Section: Discussionmentioning
confidence: 72%
“…Studies in humans also show that 100% oxygen stimulus inhibits both ventilatory and sympathetic chemoreflex response. 12,13,18,21,28 It is then wise to consider the reduction of MSNA observed in our study as the effect of carotid body inhibition by hyperoxia, but we cannot exclude the role of the local vascular effects. The interpretation of circulatory parameters during hyperoxia in hypertensive subjects need further study.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations